Socioecological Risk and Protective Factors for Smoking Among Active Duty U.S. Military Personnel. Issue 7 (28th June 2018) - Brown, Janice M; Anderson Goodell, Erin M; Williams, Jason; Bray, Robert M
Abstract: Introduction: Cigarette smoking can have negative consequences in military populations including injury, reduced physical endurance, higher frequency of sick days, and reduced combat readiness. This study used the socioecological model to understand individual, interpersonal, and organizational influences on cigarette smoking among military members. Materials and Methods: The sample for this secondary analysis was drawn from personnel at 24 large U.S. military installations, six from each service branch. Analyses included 4, 728 personnel who were classified as current cigarette smokers. Generalized linear mixed models were used to estimate the associations among risk and protective factors from multiple ecological levels for smoking intensity and nicotine dependence. Results: Smoking to fit in with one's unit, being in the Army, smoking as a reaction to stress, and work-related stressors were all related to increased intensity of smoking and nicotine dependence. More active coping was associated with lower nicotine dependence and reduced smoking intensity. Conclusion: Results based on the socioecological model identify influencing factors and suggest possible interventions for smoking cessation. Reducing tobacco use in the military will require coordinated interventions that address multilevel determinants of use and improve military health. This is important to the strategic alignment of policy and services across the continuum of health care needs.